The Representation of the CORRUPTION Concept in the Ukrainian Aphorisms Stock (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The article deals with the linguistic and mental CORRUPTION concept represented in the Ukrainian aphorisms stock. The relevance of the problem is caused by the necessity of detailed study of the concept CORRUPTION in the Ukrainian concept sphere that provides accounting of its components. The aphorisms illustrate philosophical issues, sometimes have political content, often interpret moral and ethical issues or concern everyday situations. Each aphorism is a concise source of original thought, built with the help of word games and paradoxes, puns, comparisons, antithesis, oxymoron, graduation, etc. The paper studies the concept as the content side of the verbal sign, which is the concept belonging to the mental, spiritual or vital material sphere of human existence, developed and embodied by social experience of people. The verbalization of the concept in political aphorisms was explored on the basis of publicistic aphorisms. Political aphorisms considered as statements of politicians, public figures and artists. The paper reveals the concept semantics content of this notion with nuclear and peripheral components. Attention is drawn to the fact that nuclear components of concept CORRUPTION are “corruption”, “bribery”, “theft”; peripheral components are “power”, “struggle for power”, “crime”, “fight against corruption”, “nepotism” and so on. The article is also focused on new knowledge of CORRUPTION concept conceptualization. We investigate one of the most popular methods of creating stylistic effect – metaphorization. Illustrated aphorisms encourage the understanding of universal moral values and national priorities.
Keywords: aphorism; political aphorism; concept; metaphor; nuclear seme; peripheral seme